Facility-level implementation strategies in early childhood education and care to enhance adherence to a provincial physical activity standard: Protocol for the Good Start Matters ATP+ randomised controlled trial - Louise C. Mâsse; Chris Wright; E. Jean Buckler; Olivia De-Jongh González; Luke Wolfenden; Guy Faulkner; Valerie Carson; Viviene Temple; Mariana Brussoni; Sana Fakih; Karen Sauve; Iyoma Edache; et al. (PLoS ONE, 2025)
Early childhood education and care (ECEC) facilities represent an important setting to support the healthy development during early childhood through the promotion of active play (AP) and fundamental movement skills (FMS). A mandatory AP standard was enforced in 2017 for licensed ECEC centres in the province of British Columbia, Canada. In conjunction with the AP standard, a suite of capacity building resources were administered (Appetite to Play), which improved the knowledge and confidence of early childhood educators in implementing AP and FMS development activities. Child outcomes were not measured. With implementation of AP practices degrading over time, we set out to enhance existing ATP resources and developed an advanced mobile app-based professional development program title “Appetite to Play Plus (ATP+)”. ATP+ focuses on implementation strategies that integrate AP and FMS into scheduling and curriculum planning and on creating a supportive environment for AP in ECEC facilities. The purpose of the research is to investigate whether advanced mobile app-based training focused on implementation strategies and practical resources for early childhood educators and managers: 1) enhances adherence to the British Columbia Director of Licensing Standard of Practice for AP, and 2) improves 2.5- to 5.9-year-old children’s AP and FMS over a 12-week period. We hypothesise that centres randomised to the ATP+ intervention will: 1) demonstrate greater adherence to the AP standards in comparison to those assigned to the waitlist control group, and 2) children attending intervention centres will spend more time in AP while in care and have greater increases in their FMS scores. A hierarchical mixed effect model incorporating both fixed and random effects at the ECEC centre and child levels will test the impact of ATP + , while considering that children, educators and managers are clustered within ECEC centres. Trial registration ClinicalTrials.gov NCT05669378